PERSEPSI MASYARAKAT TERHADAP KEBERHASILAN LAPANGAN BENTENG SEBAGAI RUANG TERBUKA PUBLIK - Purba, Ferdinan Hunter; Naibaho, Polin; Rajagukguk, Williater (ALUR :Jurnal Arsitektur, 2018)
Public open space is a vital element in a city because of its presence in high intensity activities. One of thepublic open spaces in the middle of Medan city is Benteng Square. Benteng Square is included as an activepublic open space for activities, sports and ceremonies. Benteng Square is owned by the city governmentof Medan and the management is the Kodim 0201 / BB Medan, but its use is not maximal at this time.Therefore, the research is needed to find out how far the level of success and public perception ofBenteng Square. This research is quantitative research. The main data is a questionnaire which is thenanalyzed descriptively and quantitatively with a Likert scale. The results of the study show that theBenteng Square was successful in its function as a public open space.